Characterization of all Surgical Specimens Provided by a Portuguese Department of Ophthalmology over a 13 Year Period - Ferreira Mendes, José (2017)
Introduction: We intend to evaluate clinically, topographically and morphologically all surgical specimens sent by the Department of Ophthalmology of Hospital de Braga to the Department of Pathology of the same hospital.Material and Methods: Two hundred and fifty eight surgically obtained specimens, from the Department of Ophthalmology of Hospital de Braga, analyzed in the Department of Pathology, from January 2002 to June 2015, were characterized. Data was arranged according to year, age, sex, topography and morphological diagnosis according to the SNOMED® coding system.Results: Mean age at time of diagnosis was 54.6 years old; 52.3% were male subjects. The number of specimens was relatively stable until the year 2010, with a significant increase between 2011 and 2013. Most specimens sent corresponded to eyelid (54.7%), followed by conjunctiva (26.7%); the most common pathological diagnosis was malignant epithelial lesions (22.48%), followed by melanocytic tumours (22.09%) and benign epithelial lesions (17.05%).Discussion: The results are distinct from previous publications presumably because of differences between the populations submitted to analysis.Conclusion: This is the first indexed publication characterizing surgical specimens from a Department of Ophthalmology in Portugal; moreover, it also includes an extensive review of global epidemiological data about ophthalmic surgical specimens.